BIOEKOLOGI TUMBUHAN POHON KELAPA (Cocos nucifera) DI PANTAI KURANJI, KABUPATEN LOMBOK BARAT - Sulistia Febriani; Muhammad Zulhilmi; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
Coastal ecosystems consist of lively habitats marked by elevated temperatures, salinity levels, significant wind exposure, and minimal soil moisture, all of which affect the growth and spread of plant species. The coconut tree (Cocos nucifera) stands out as a prevalent species in tropical coastal regions owing to its exceptional ability to adapt. The objective of this research is to assess the bioecological traits of coconut trees located at Kuranji Beach, in the West Lombok Regency, through direct environmental observations. The study utilized a descriptive observational approach, focusing on measurements of soil temperature, soil acidity, and moisture levels in the soil. Findings revealed that the soil temperature was at 35°C, soil pH measured between 7 and 7.5 (indicating neutrality to slight alkalinity), while soil moisture was identified as low (indicating dry conditions). These results suggest that the coastal habitat imposes challenges for plant development; nonetheless, coconut trees show significant adaptation capabilities through both structural and functional responses. This research highlights the crucial ecological role that coconut vegetation plays in sustaining coastal durability and resilience.